Chirality in biological nanospaces reactions in active sites - Nandi, Nilashis (Boca Raton : CRC Press, 2012)
"Vital life processes occur within the active sites of large biological macromolecules such as proteins, nucleic acids, and lipids. These nanodimensional structures greatly accelerate biological reactions. The chirality of the reactants also has a strong influence on the process, but its importance in such biological reactions has only recently begun to be understood. This book explores the influence of chirality on reaction mechanisms in such biological nanospaces. The text addresses the influence of the chirality of amino acid and sugar in the active sites of transferase, oxidoreductases, hydrolases, lysases, isomerase, ligases, and other systems. It also covers ribosomal architecture"--Provided by publisher.
"Discusses the relationship of molecular chirality and biology. Diverse natural biological molecules are dissymmetric and are discussed. Also described are the interactions between molecules in a confined state in biological systems and the resulting fascinating properties"--Provided by publisher.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Chirality; Biomolecules; Electronic books